Molecular characterization of Tfap2A and Tfap2B in GABAergic neurons in the developing cerebellum - Chin, Priscilla Si Wai (2016)
The cerebellum is a crucial part of the brain that plays a vital role in our daily living. Research has shown that cerebellar defects and damages are associated with neurological disorders such as autistic spectrum disorder (ASD). Although the cerebellum has been researched extensively over the past few decades, mechanisms underlying the cerebellar functions are still not fully understood. The cerebellar circuitry plays an essential role in the cerebellum's functionality, yet, the development of this circuitry framework is not fully characterized. Transcription factors are known to be integral in the development of the central nervous system. We have found two isoforms of the Tfap2 family of transcription factors, Tfap2A and Tfap2B, to be expressed in the cerebellum, especially in the cortical region. However, their function in the cerebellum is not comprehended. In this study, we aim to characterize the temporal and spatial expression of Tfap2A and Tfap2B using molecular experiments such as immunohistochemistry. Our results revealed they are expressed specifically in GABAergic inhibitory neuronal subtypes of the cerebellar cortex and in the deep cerebellar nuclei during development, suggestive of their oligopotent properties. Their expression also persists into adulthood, indicating their importance in both development and maintenance of these inhibitory neurons.